Proenkephalin A and bioactive adrenomedullin are useful for risk prognostication in cardiac surgery - Hill, Aileen; Bergmann, Deborah; Schulte, Janin; Zayat, Rashad; Marx, Gernot; Simon, Tim-Philipp; Mossanen, Jana; Brücken, Anne; Stoppe, Christian (Frontiers in Cardiovascular Medicine, 2023)
Introduction Various clinical scores have been developed to predict organ dysfunction and mortality in patients undergoing cardiac surgery, but outcome prediction may be inaccurate for some patient groups. Proenkephalin A (penKid) and bioactive adrenomedullin (bio-ADM) have emerged as promising biomarkers correlating with shock and organ dysfunction. This imposes the question of whether they can be used as prognostic biomarkers for risk stratification in the perioperative setting of cardiac surgery. Methods Patients undergoing cardiac surgery were prospectively enrolled in this observational study. PenKid and bio-ADM plasma levels, as well as markers evaluating inflammation and organ dysfunction, were measured at five perioperative time points from before the induction of anesthesia to up to 48 h postoperatively. Clinical data regarding organ dysfunction and patient outcomes were recorded during the intensive care unit (ICU)-stay with a special focus on acute kidney injury (AKI). Results In 136 patients undergoing cardiac surgery, the bio-ADM levels increased and the penKid levels decreased significantly over time. PenKid was associated with chronic kidney disease (CKD), the incidence of AKI, and renal replacement therapy (RRT). Bio-ADM was associated with lactate and the need for vasopressors. PenKid was useful to predict an ICU-length of stay (LOS)>1 day and added prognostic value to the European System for Cardiac Operative Risk Evaluation Score (EuroSCORE) II when measured after the end of cardiopulmonary bypass and 24 h after cardiac surgery. For bio-ADM, the same was true when measured 24 h after surgery. PenKid also added prognostic value to the EuroSCORE II for the combined outcome “ICU length of stay >1 day and in-hospital mortality.” Conclusion The combination of preoperative EuroSCORE II and intraoperative measurement of penKid may be more useful to predict a prolonged ICU LOS and increased mortality than EuroSCORE II alone. Bio-ADM correlates with markers of shock. More research is encouraged for early risk stratification and validation of penKid and bio-ADM as a tool involved in clinical decisions, which may enable the early initiation of organ protective strategies.